Effect of Counter Cation on Alkaline Reaction of β-O-4-Type Substructure in Lignin. (4th March 2019) - Kato, Yuishin; Shimizu, Satoko; Akiyama, Takuya; Yokoyama, Tomoya; Matsumoto, Yuji
Abstract : This study aimed to clarify the effects of counter cations on the alkaline-induced β - O -4 bond cleavage and further reactions of β - O -4-type substructures in lignin. For this purpose, a non-phenolic β - O -4-type lignin model compound, the erythro isomer of 2-(2-methoxyphenoxy)-1-(3, 4-dimethoxyphenyl)propane-1, 3-diol (veratrylglycerol- β -guaiacyl ether), was treated in a 100% water solution or an aqueous methanol, ethanol, or 1, 4-dioxane solution containing LiOH, NaOH, or CsOH as an alkaline source at 150 °C. The rates of β - O -4 bond cleavage were in the order of CsOH > NaOH > LiOH in all solvents. This order can rationally be attributed to the strength of the interactions between HO – and the counter cations. Because Cs + has the lowest positive charge density among the counter cations and hence interacts with HO – most weakly, HO – can exert its reactivity most actively in the reactions using CsOH. We also discuss how the counter cations affect the profile of reaction products.